Fate, Divine Will and Narrative Concept in the Homeric Epics - Sarischoulēs, Eustratios (Mythos, 2016)
Human action and its consequences in the Iliad and the Odyssey are determined neither by fate nor by the gods. The reconstruction of the concept actually depicted in Homer confirms no conflict between fate and the gods as co-existing forces but reflects the personal motives of active agents, both human and divine, as the basis that underpins the sequence of events in both epics. Nature and individual purposes of each and every active agent, personal desires and aims harboured by human and divine actors shape these motives in a world that perceives life as a path leading to death with no preordained events but as a compound of actual alternatives. In this world every single action is attributed to choices, has its reasons, elicits reactions or rather consequences. As a result, the particular active agent takes resposibility for each choice he makes and shapes his own future. Various forms of divination as well as the perception of omens confirm this conclusion, as predictions in the Homeric epics do not point out predetermined events but motives, decisions and actions of the human actor involved.